2016
DOI: 10.1007/s12664-016-0643-2
|View full text |Cite
|
Sign up to set email alerts
|

Intragastric balloon as a novel modality for weight loss in patients with cirrhosis and morbid obesity awaiting liver transplantation

Abstract: Intragastric balloon placement is a useful modality for promoting short-term weight loss and thereby making morbidly obese recipients fit for liver transplantation surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 17 publications
0
25
0
2
Order By: Relevance
“…Small studies reporting outcomes in patients with decompensated cirrhosis and CSPH [68] show an acceptable safety profile. However, the presence of gastric varices, large esophageal varices, or severe portal hypertensive gastropathy, all of which are commonly found in the decompensated patient, are contraindications for this procedure [69,70].…”
Section: Obesity Before Liver Transplantationmentioning
confidence: 99%
“…Small studies reporting outcomes in patients with decompensated cirrhosis and CSPH [68] show an acceptable safety profile. However, the presence of gastric varices, large esophageal varices, or severe portal hypertensive gastropathy, all of which are commonly found in the decompensated patient, are contraindications for this procedure [69,70].…”
Section: Obesity Before Liver Transplantationmentioning
confidence: 99%
“…21,22 Recently, there has been growing interest in the possibility of endoluminal treatments for obesity in individuals with high surgical risk. An endoscopic intragastric balloon implant in this group of patients, which is an attractive alternative, has presented satisfactory results in studies conducted by Choudhary et al 25 A case report by Campsen et al 26 showed the realization of adjustable gastric band implantation during a liver transplant had satisfactory results after 6 months. Heimbach et al 27 reported the combined realization of liver transplantation and vertical sleeve gastrectomy in seven patients with one case of a fistula on the staple line and zero mortality.…”
Section: Resultsmentioning
confidence: 93%
“…This approach may also help select candidates who have a higher likelihood of success owing to inherent motivation and compliance required to undergo a procedure [15,16]. Not only a bridge to bariatric surgery, but endobariatric therapies may also have a role in bridging to organ transplantation, allowing pretransplant candidates to meet transplant eligibility and decrease posttransplant morbidity and mortality, as demonstrated in previous studies of heart and liver transplants [17,18]. Endobariatric therapies are already proven metabolic therapies with a potential utility in patients with primary diabetes or nonalcoholic fatty liver disease [19,20].…”
Section: The Role Of Endobariatric Therapies and Appropriate Candidatesmentioning
confidence: 99%